Isolation and characterization of bacteria isolated from decayed fruits / Intan Munirah Zulkahar - Zulkahar, Intan Munirah (2017)
Malaysia paradies for local fruits such as banana (Musa paradisiaca), papaya (Carica papaya L.) and pineapple ( Ananas comosus L.). Bacteria easily spoiled the local fruits which caused change in the appearance, colour and smell of the fruits. Therefore, this study were aim to isolate and identify pathogenic bacteria by using morphological and molecular methods. Decayed fruits such as banana, papaya and pineapple samples were obtained from fruits shop at Kuala Pilah Negeri Sembilan district. In this study, six bacteria strain were successfully isolated known as P1, P2, B1, B2, N1 and N2 bacteria. Gram strain results demonstrated that one bacteria, B1 give a positive result while others five bacteria which were P1, P2, B2, N1 and N2 showed negative results with rod-shaped appearance. In addition, P1, P2, B1, B2, N1 and N2 bacteria colonies observation showed circular, entire, raised, smooth and shinning however it differed in term of size and optical characteristics. In addition, biochemical tests showed P1 and P2 bacteria belong to Klebsiella sp. and Escherichia sp. meanwhile others bacteria failed to give positive results. However, molecular analysis showed a negative results for P1 and P2 bacteria. Therefore in this study, bacteria samples from decayed fruits belong to Klebsiella sp. and Escherichia sp. Molecular analysis was recommended to comfirm the bacteria species.